2021
DOI: 10.1186/s40478-021-01265-9
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous supratentorial and infratentorial oligodendrogliomas with incongruous IDH1 mutations, a case report

Abstract: Infratentorial oligodendrogliomas, a rare pathological entity, are generally considered metastatic lesions from supratentorial primary tumors. Here, we report the case of a 23-year-old man presenting with a histopathologically confirmed right precentral gyrus grade 2 oligodendroglioma and a concurrent pontine grade 3 oligodendroglioma. The pontine lesion was biopsied approximately a year after the biopsy of the precentral lesion due to disease progression despite 4 cycles of procarbazine-CCNU-vincristine (PCV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Agopyan-Miu et al [ 12 ] reported a patient with synchronous supratentorial and infratentorial oligodendrogliomas. They resected the lesions sequentially and subjected them to genetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Agopyan-Miu et al [ 12 ] reported a patient with synchronous supratentorial and infratentorial oligodendrogliomas. They resected the lesions sequentially and subjected them to genetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the frontal lobe, other locations in the cerebrum include the temporal, parietal or rarely occipital lobe. Very rare case reports describe oligodendrogliomas arising in the posterior fossa, brainstem or demonstrating diffuse involvement of multiple bilateral brain areas in a gliomatosis cerebri pattern (26)(27)(28). Recurrent disease is more likely to show leptomeningeal or intraventricular spread (27,29,30).…”
Section: Oligodendroglioma Idh-mutant and 1p/19q-codeleted Cns Who Gr...mentioning
confidence: 99%
“…One speculation is that the right parietal lesion is a secondary lesion derived from the frontal tumor. The different IDH mutations may suggest an evolved trajectory resulting in more invasive clones able to metastasize transmission (8,10). In this case, glioma cells in the parietal lesion probably possess a more remarkable ability to metastasize through cerebrospinal fluid or cortical tract fibers.…”
Section: Discussionmentioning
confidence: 95%
“…The simultaneous presence of multiple foci, remarkably homologous foci with different histopathologic compositions, is rare in all types of gliomas (7). Based on radiologic and/or pathologic features, complicating lesions can be divided into multifocal and multicentric categories (8). Multicentric gliomas fail to differentiate due to genetic defects in stem cells, resulting in defective, highly proliferative cell populations that form tumor centers (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation